Prenatal Diagnosis Of Tay-Sachs Disease - Özyüncü, Özgür; Başaran, Derman; Özkara, Asuman; Topçu, Meral; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: To emphasize the efficacy and safety of the prenatal invasive procedures for prenatal diagnosis of Tay-Sachs disease. STUDY DESIGN: In this case series, the results of the prenatal invasive procedures that were performed for diagnosing Tay-Sachs disease in 8 patients between 2000 and 2008 are reported. The samples were obtained by chorionic villus sampling or by cordocentesis. Total hexosaminidase level and the percentage of isoenzyme ß-Hexosaminidase A were measured in fetal samples. RESULTS: There were 8 patients in diagnosed prenatatlly between 2000-2008. Sufficient material for enzyme analysis was obtained without any complications. Total hexosaminidase levels and the percentage of hexosaminidase were in normal limits in all fetal samples. All pregnancies ended up with uneventful term births. CONCLUSION: Tay-Sachs disease can be diagnosed prenatally by measuring hexosaminidase enzyme activity in fetal tissue samples with an acceptable complication rate. Prenatal diagnosis should be offered to families who have affected siblings with Tay-Sachs disease.